AN ENERGY EFFICIENT SYSTEM FOR WIRELESS SENSOR NETWORKS - Dr.M.Paul Daniel, Dr.P.Sreenivasulu,Dr Seelam Koteswararao,Daggubati Sunil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This paper describe a unique method for energy-aware management of sensor networks, one that extends the useful lifetime of sensors while keeping in place all the desirable quality-of-service qualities associated with the delivery of sensed data. This paper also uses dynamic route setting and medium access arbitration to reduce sensor burnout and prolong battery life. It provides an introduction to dynamic source routing and details a MAC based on time division multiple access (TDMA). As a result, the proposed APCRP-MAC Protocol increases the longevity of sensor networks while decreasing their power requirements.Our extensive results in the Network Simulator (NS2) demonstrate that the new clustering and routing algorithms scale effectively and converge quickly for large-scale dynamic sensors.